IMPLEMENTASI SISTEM MANAJEMEN DALAM PENGOLAHAN DATA LAUNDRY STUDY KASUS “RICA UTAMI” - Kurniawan Wahyu Haryanto; Merlin Wahyu Supriati (STMIK YADIKA BANGIL, 2019)
Laundry is a business that is engaged in providing services, laundry work includes washing clothes, curtains, dolls and so forth. Rica Utami Laundry is a business that is engaged in laundry service providers founded by Ms. Rica Utami as the laundry business owner. At Rica Utami Laundry the data processing in this business is still using a manual process, from processing the laundry transaction data to making laundry transaction reports all of which are still processed in a book. This manual system is very inhibiting the processing of laundry data itself. Based on this problem, the authors raise a problem entitled